The Songs of the Minnesinger, Prince Wizlaw of Rügen : with modern transcription of his melodies and English translations of this verse, - Thomas, J.W (Online access: OAPEN DOAB Directory of Open Access Books., 1967)
This work originally published in 1967 was the first to treat Wizlaw in his three roles of composer, poet, and sovereign and to present his poetry in English. Thomas and Seagrave also include a bibliography, translations and music transcriptions of all his songs, and photographic reproductions of corresponding folios of the Jena manuscript.